Systematic Investigation of FLOWERING LOCUS T-Like Poaceae Gene Families Identifies the Short-Day Expressed Flowering Pathway Gene, TaFT3 in Wheat (Triticum aestivum L.) - Halliwell, Joanna; Borrill, Philippa; Gordon, Anna; Kowalczyk, Radoslaw; Pagano, Marina L.; Saccomanno, Benedetta; Bentley, Alison R.; Uauy, Cristobal; Cockram, James (Frontiers in Plant Science, 2016)
To date, a small number of major flowering time loci have been identified in the related Triticeae crops, bread wheat (Triticum aestivum), durum wheat (T. durum) and barley (Hordeum vulgare). Natural genetic variants at these loci result in major phenotypic changes which have adapted crops to the novel environments encountered during the spread of agriculture. The polyploid nature of bread and durum wheat means that major flowering time loci in which recessive alleles confer adaptive advantage in related diploid species have not been readily identified. One such example is the PPD-H2 flowering time locus encoded by FLOWERING LOCUS T 3 (HvFT3) in the diploid crop barley, forin which recessive mutant alleles confer delayed flowering under short day (SD) photoperiods. In autumn- sown barley, such alleles aid the repression of flowering over the winter, which help prevent the development of cold-sensitive floral organs until the onset of inductive long day (LD) photoperiods the following spring. While the identification of orthologous loci in wheat could provide breeders with alternative mechanisms to fine tune flowering time, systematic identification of wheat orthologues of HvFT3 has not been reported. Here, we characterise the FT gene families in six Poaceae species, identifying novel members in all taxa investigated, as well as FT3 homoeologues from the A, B and D genomes of hexaploid (TaFT3) and tetraploid wheat. Sequence analysis shows TaFT3 homoeologues display high similarity to the HvFT3 coding region (95-96 %) and predicted protein (96-97 %), with conservation of intron/exon structure across the five cereal species investigated. Genetic mapping and comparative analyses in hexaploid and tetraploid wheat find TaFT3 homoeologues map to the long arms of the group 1 chromosomes, collinear to HvFT3 in barley and FT3 orthologues in rice, foxtail millet and brachypodium. Genome-specific expression analyses show FT3 homoeologues in tetraploid and hexaploid wheat are upregulated under SD photoperiods, but not under LDs, analogous to the expression of HvFT3. Collectively, these results indicate that functional wheat orthologues of HvFT3 have been identified. The molecular resources generated here provide the foundation for engineering a novel major flowering time locus in wheat using forward or reverse genetics